2021
DOI: 10.1128/spectrum.00274-21
|View full text |Cite
|
Sign up to set email alerts
|

A New Thienopyrimidinone Chemotype Shows Multistage Activity against Plasmodium falciparum, Including Artemisinin-Resistant Parasites

Abstract: This work reports a new chemical structure that (i) displays activity against the human malaria parasite Plasmodium falciparum at 3 stages of the parasitic cycle (blood stage, hepatic stage, and sexual stages), (ii) remains active against parasites that are resistant to the first-line treatment recommended by the World Health Organization (WHO) for the treatment of severe malaria (artemisinins), and (iii) reduces transmission of the parasite to the mosquito vector in a mouse model. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…When Suzuki–Miyaura coupling was performed on compound 1 or 3, applying the reaction conditions used for the synthesis of M1 metabolites, 10 we observed the dehalogenation of the starting material, which complicated the purification. Therefore, we decided to perform Suzuki–Miyaura coupling on 2 with conditions from the literature and previously used in our lab.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When Suzuki–Miyaura coupling was performed on compound 1 or 3, applying the reaction conditions used for the synthesis of M1 metabolites, 10 we observed the dehalogenation of the starting material, which complicated the purification. Therefore, we decided to perform Suzuki–Miyaura coupling on 2 with conditions from the literature and previously used in our lab.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the in vivo activity in P. berghei infected mice was only achieved with the addition of 1-aminobenzotriazole, a pan-CYP450 inhibitor. 10 Therefore, the synthesis of new thieno[3,2- d ]pyrimidines to afford a new hit compound with improved metabolic stability and similar activity profile was initiated. We also expected to obtain new antiplasmodial SAR data on the thieno[3,2- d ]pyrimidine series.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary in vivo evaluation revealed that 57j reduced parasitemia by 45% compared to untreated infected mice, proving that its antiplasmodial activity was preserved in vivo. Bosson-Vanga et al discovered 57j displayed activity on P. falciparum at the three stages of the parasite cycle (erythrocytic, hepatic and sexual stages) and reduced transmission of the parasite in a mouse model [9]. However, the original mechanism of action of these compounds remains to be elucidated.…”
Section: % Inhibition Pf3d7mentioning
confidence: 99%
“…In a recent review, Ali et al summed up the biological activities of the thieno [2,3d]pyrimidine scaffold until the end of 2018, with a particular attention provided onto their anticancer activities [2]. Due to our interest in the development of new anti-infective compounds [4][5][6][7][8][9], the objective of the present review is to provide an overview of the access routes to thienopyrimidine derivatives and to discuss the significance of this scaffold for the discovery of anti-infective drugs. In this review, we have collected all references until September 2021 involving the three isomers presented above with anti-infective properties.…”
Section: Introductionmentioning
confidence: 99%